Deep Brain Stimulation during Pregnancy and Delivery: Experience from a Series of “DBS Babies” - Scelzo, Emma; Mehrkens, Jan H.; Bötzel, Kai; Krack, Paul; Mendes, Alexandre; Chabardès, Stéphan; Polosan, Mircea; Seigneuret, Eric; Moro, Elena; Fraix, Valerie (Frontiers in Neurology, 2015)
Introduction: Deep brain stimulation (DBS) is widely used to improve quality of life in movement disorders and psychiatric diseases. Even though the ability to have children has a big impact on patients’ life, only a few studies describe the role of DBS in pregnancy. Objective: To describe risks and management of women treated by DBS for disabling movement disorders (MD) or psychiatric diseases during pregnancy and delivery. Methods: We report a retrospective case series of women, followed in two DBS centers, who became pregnant and went on to give birth to a child while suffering from disabling MD or psychiatric diseases (Parkinson’s disease (PD), dystonia, Tourette’s syndrome (TS), Obsessive Compulsive Disorder (OCD)) treated by DBS. Clinical status, complications and management before, during and after pregnancy are reported. Two illustrative cases are described in greater detail. Results: DBS improved motor and behavioural disorders in all patients and allowed reduction in, or even total interruption of disease-specific medication during pregnancy. With the exception of the spontaneous early abortion of one fetus in a twin pregnancy, all pregnancies were uneventful in terms of obstetric and pediatric management. DBS parameters were adjusted in five patients in order to limit clinical worsening during pregnancy. Implanted material limited breast-feeding in one patient because of local pain at submammal stimulator site and led to local discomfort related to stretching of the cable with increasing belly size in another patient whose stimulator was implanted in the abdominal wall. Conclusions: Not only is it safe for young women with MD, TS and OCD who have a DBS-System implanted to become pregnant and give birth to a baby but DBS seems to be the key to becoming pregnant, having children, and thus greatly improves quality of life.